1998
DOI: 10.1161/01.cir.98.25.2822
|View full text |Cite
|
Sign up to set email alerts
|

Increased Formation of Distinct F 2 Isoprostanes in Hypercholesterolemia

Abstract: Background-F 2 isoprostanes are stable, free radical-catalyzed products of arachidonic acid that reflect lipid peroxidation in vivo. Methods and Results-Specific assays were developed by use of mass spectrometry for the F 2 isoprostanes iPF 2␣ -III and iPF 2␣ -VI and arachidonic acid (AA). Urinary excretion of the 2 F 2 isoprostanes was significantly increased in hypercholesterolemic patients, whereas substrate AA in urine did not differ between the groups. iPF 2␣ -III (pmol/mmol creatinine) was elevated (PϽ0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
159
1
7

Year Published

2000
2000
2006
2006

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(172 citation statements)
references
References 49 publications
5
159
1
7
Order By: Relevance
“…While F 2 -Isoprostane, free radical-catalyzed products of arachidonic acid, have been widely studied as potential biomarkers of oxidant stress [2,14,[31][32][33], there are no investigations, as far as we are aware, that have simultaneously monitored multiple distinct lipid oxidation products from blood to determine which are more tightly correlated with cardiovascular disease prevalence, and thus potentially of greatest clinical relevance. Remarkably, studies examining lipid oxidation species within excised human atheroma from symptomatic versus nonsymptomatic carotid endarterectomy specimens identified 9-HETE, and less so F 2 -Isoprostane, as abundant fatty acid oxidation products within atheroma from symptomatic vascular lesions [34].…”
Section: Discussionmentioning
confidence: 99%
“…While F 2 -Isoprostane, free radical-catalyzed products of arachidonic acid, have been widely studied as potential biomarkers of oxidant stress [2,14,[31][32][33], there are no investigations, as far as we are aware, that have simultaneously monitored multiple distinct lipid oxidation products from blood to determine which are more tightly correlated with cardiovascular disease prevalence, and thus potentially of greatest clinical relevance. Remarkably, studies examining lipid oxidation species within excised human atheroma from symptomatic versus nonsymptomatic carotid endarterectomy specimens identified 9-HETE, and less so F 2 -Isoprostane, as abundant fatty acid oxidation products within atheroma from symptomatic vascular lesions [34].…”
Section: Discussionmentioning
confidence: 99%
“…These models allow for flexibility, testing for treatment effects as well as examining for period (time) and order effects (ie, testing for carry over effects), and adjusting for important baseline and time-dependent (ie serum cholesterol levels) covariates. Recently published manuscripts (Reilly et al, 1998;Palombo et al, 1999;Davi et al, 1997Davi et al, , 1999 demonstrated that serum cholesterol affects isoprostane levels, and previous research has suggested that blood tocopherol concentrations may be influenced by serum cholesterol levels. The alcohol treatments in this study significantly altered serum total cholesterol levels (Baer et al, 2002); therefore for vitamin E and isoprostane samples, we used a residual method to adjust concentration for the total serum cholesterol measurement obtained at the same time.…”
Section: Discussionmentioning
confidence: 99%
“…This group demonstrated that F 2 -isoprostanes were superior to other biomarkers used as indices of lipid peroxidation in vivo, including malondialdeyde (MDA) (Longmire et al, 1994). Levels of F 2 -isoprostanes in body fluids are elevated by conditions that are thought to be associated with free radical-induced oxidative stress, including smoking (Morrow et al, 1995;Reilly et al, 1996), hypercholesterolemia (Davi et al, 1997;Reilly et al, 1998;Palombo et al, 1999), diabetes (Davi et al, 1999), and acute and chronic alcoholic liver disease Meagher et al, 1999). Recent research suggests a role for oxidative stress in breast cancer (Kumar et al, 1991;Thangaraju et al, 1994;Li et al, 1999;Novak & Woodcroft, 2000;Ray et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Isoprostanes are also increased in association with such risk factors as hypercholesterolemia 7 and diabetes mellitus, 4 which are relevant in the development of ischemic vascular disease. Notably, it has been demonstrated that hypercholesterolemia 28 and diabetes mellitus, 29 well-known risk factors for the progression and destabilization of atherosclerotic plaque, are associated with an inflammatory response that renders the tissues more vulnerable to ischemic episodes.…”
Section: Fontana Et Al 8-iso-pgf 2␣ and Neutrophil Adhesionmentioning
confidence: 99%
“…F 2 -Isoprostanes can be measured in both plasma and urine 1 and have been shown to be increased in association with clinical conditions such as coronary ischemia/reperfusion syndrome, 2 adult respiratory distress syndrome, 3 diabetes mellitus, 4 and chronic pulmonary disease. 5 They are also increased in association with several risk factors for the development of ischemic vascular disease, including cigarette smoking, 6 hypercholesterolemia, 7 and hyperhomocysteinemia. 8 Thus, analysis of F 2 -isoprostanes has emerged as a specific and reliable marker of oxidant stress in vivo.…”
mentioning
confidence: 99%